2014
DOI: 10.5194/angeo-32-41-2014
|View full text |Cite
|
Sign up to set email alerts
|

China's dimming and brightening: evidence, causes and hydrological implications

Abstract: Abstract. There is growing evidence that, corresponding to global dimming and brightening, surface solar radiation and sunshine hours over China have undergone decadal fluctuations during the 1960s-2000s. The results of a number of these analyses are, however, very different. In this study, we synthesize reliable results and conclusively address recent advances and insufficiencies in studies on dimming and brightening in China. A temporally and spatially prevalent dimming trend is noted in surface solar radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 99 publications
(249 reference statements)
10
60
1
5
Order By: Relevance
“…4a). The averaged urban dimming rate in China is slightly lower than that obtained in previous studies (Wang et al, 2013;Wang and Yang, 2014) because a few megacities without available nearby rural stations were excluded from this study. Dimming in rural and sparsely populated areas was also noted in Europe, Japan, New Zealand, Egypt, and the greater Tel Aviv region by previous studies (e.g., Liley, 2009;Robaa, 2009;Stanhill and Cohen, 2009;Sanroma et al, 2010;Tanaka et al, 2016).…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…4a). The averaged urban dimming rate in China is slightly lower than that obtained in previous studies (Wang et al, 2013;Wang and Yang, 2014) because a few megacities without available nearby rural stations were excluded from this study. Dimming in rural and sparsely populated areas was also noted in Europe, Japan, New Zealand, Egypt, and the greater Tel Aviv region by previous studies (e.g., Liley, 2009;Robaa, 2009;Stanhill and Cohen, 2009;Sanroma et al, 2010;Tanaka et al, 2016).…”
Section: Methodsmentioning
confidence: 54%
“…Subsequently, a transition from a decrease to an increase in surface solar radiation occurred in many regions of the world from the mid-1980s on the order of 1 to 4 W m −2 (Wild et al, 2005;Wild, 2012Wild, , 2016. These phenomena are popularly known as "global dimming and brightening", where "global" originally referred to "global radiation" as a synonym for surface solar radiation but is often interpreted in terms of a global-scale dimension (Wild, 2009(Wild, , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intense human activity releases vast amounts of tiny particles and greenhouse gases into the atmosphere. The increase in aerosols in the atmosphere induces strong reflection of incoming solar radiation and rapid decline in solar radiation absorption (Wang and Yang 2014). Thus, a strong trend of decline in solar radiation has persisted in China since the 1960s (Che et al 2005).…”
Section: Changes In Climate Variable and Maize Yieldmentioning
confidence: 99%
“…In earlier studies, Ohmura and Lang (1989) proposed cloud changes as the cause of global dimming, while a few studies (Stanhill and Moreshet, 1992;Liepert et al, 1994) attributed the radiation changes to aerosols. Previous studies until now generally pointed to the dominant role of aerosols in bringing about global dimming and brightening in China and Japan (Kaiser and Qian, 2002;Hayasaka et al, 2006;Qian et al, 2006;Norris and Wild, 2009;Kudo et al, 2012;Wang et al, 2012;Wang and Yang, 2014), in Europe (Norris and Wild, 2007;Ruckstuhl et al, 2008;Wang et al, 2012), and globally (Wild et al, 2005) based on a variety of approaches to estimating or inferring clear-sky (or cloud-free) SSR. Streets et al (2006) showed that the temporal trends of global mean aerosol optical depth (AOD) derived from emission inventories for sulfate dioxide (SO 2 ) and black carbon (BC) have a resemblance to the global brightening and dimming phenomenon.…”
Section: Introductionmentioning
confidence: 99%